Pragmatist Aesthetics, the New Literacy, and Popular Culture. A Response to Stefán Snævarr - Małecki, Wojciech (The Nordic Journal of Aesthetics, 2009)
The article is a critical response to Stefán Snævarr’s “Pragmatism and Popular Culture: Shusterman, Popular Art, and the Challenge of Visuality.”In its first part, I attempt to prove that several of Snævarr’s claims about popular culture and new media, which form the basic premises of his diagnosis of the alleged intellectual decline of the West, are either dubious or wrong. Moreover, in the context of this diagnosis, Snævarr levels some serious accusations against Richard Shusterman’s theory of popular culture, which, I believe, are ungrounded and do not do justice to the latter’s approach. Henceforth, the remainder of the article is devoted to explaining in which aspects Snævarr’s interpretation of Richard Shusterman’s theory is misguided.